2020
DOI: 10.22336/rjo.2020.37
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vivostat PRF® in Acanthamoeba keratitis

Abstract: We present a case of a 27-year-old contact lens male user who was diagnosed with Acanthamoeba keratitis. Given the inefficiency of medical treatment and high risk of corneal perforation, we decided to use Vivostat PRF®, with satisfactory results. To our knowledge, this is the first described case in medical literature in which Vivostat PRF® is used as part of Acanthamoeba keratitis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…In the present study, complications such as pigmentation and anterior synechia were observed in the PRF gel group, which is consistent with findings from other human studies 47 , 48 . However, the use of homologous L-PRF membrane proved effective in sealing severe corneal ulcers, including grade III ulcers with or without perforations and staphyloma 44 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, complications such as pigmentation and anterior synechia were observed in the PRF gel group, which is consistent with findings from other human studies 47 , 48 . However, the use of homologous L-PRF membrane proved effective in sealing severe corneal ulcers, including grade III ulcers with or without perforations and staphyloma 44 .…”
Section: Discussionsupporting
confidence: 93%
“…The inflammatory response following alkali combustion was quantified by area measurements of re-epithelialization and neovascularization 61 . Corneal wound healing is a complex process involving various factors, including proteinases, growth factors, cytokines, and lacrimal glands 62 – 64 While PRF has been used to treat corneal ulcers and has shown potential benefits, other studies have reported adverse effects on ulcer healing 43 , 47 , 48 . In this study, A-PRF gel was directly applied to the ocular surface, which has been found to prevent dehydration 65 .…”
Section: Discussionmentioning
confidence: 99%